Use of narasin for lactating ewes and feedlot lambs - Sardinha, Lairana Aline (2020)
The objective of this project was to evaluate the supply of narasin on the performance of ewes and their lambs in the lactation phase (Exp. I) and feedlot lambs (Exp. II). Experiment I: Thirty-two ewes with ten days of lactation were used, together with their lambs (s). The experimental design was randomized complete blocks. The diets consisted of 50% hay and 50% concentrate. The treatments were defined by the no narasin inclusion (N0) or inclusion of 13 mg/kg DM of narasin (N13). The experiment lasted 70 days. The inclusion of narasin did not affect the ewes DMI, however, milk production (P <0.01) and feed efficiency (FE; P = 0.02) increased. Ewes fed N13 had a greater fat (P <0.01), protein (P <0.01), lactose (P = 0.04) and total solids in milk (P <0.01). Narasin inclusion in ewes diet increased blood glucose concentration (P = 0.05) at wk 8, 9 and 10. The lambs of N0 ewes had a greater starter DMI (P <0.01) at wk 7, 8, 9 and 10; however, the ADG and BW at weaning and after weaning were similar between treatments (P< 0.05). Experiment II: The objective of the study was to evaluate in inclusion of NDF contents and the inclusion of narasin on performance, carcass parameters, rumen fermentation and histology of the papillae in feedlot lambs. Forty-four lambs were confined in a tie-stall system. The experimental design used was a randomized blocks in a 2 x 2 factorial arrangement, with factor I being the use of 20 or 25% NDF (in DM) and factor II no narasin inclusion (N0) or inclusion of 13 mg / kg DM of narasin (N13). The experiment lasted 112 days. NDF levels in the diets did not affect the ADG. However, diet containing 25% NDF resulted in increase in lambs DMI (P = 0.04) consequently, reduced the FE (P <0.01). Inclusion of 13 mg / kg DM of narasin increased SFT (P <0.01), BWT (P <0.01) and DMI (P = 0.04). The inclusion of 20% NDF resulted in increased BWT (P = 0.03) and perirenal fat weight (P = 0.05). The narasin reduced protein content (P = 0.02) and increased ether extract (EE) (P <0.01) of the meat. There was interaction between the NDF contents and the inclusion of narasin on the molar proportion of propionate (P = 0.02), and the acetate-to-propionate ratio (P <0.01). Inclusion of narasin reduced the molar ratio of acetate (P <0.01), increased ruminal pH (P = 0.05) and total SCFA concentration (P <0.01), propionate molar ratio (P = 0.02), the acetate-to-propionate ratio (P = 0.03) on the cecal fermentation. Diets containing 25% NDF and the diets containing narasin resulted in histological changes in the papillae.